The Panic of 1907 : heralding a new era of finance, capitalism, and democracy - Bruner, Robert F., 1949-; Carr, Sean D., 1969- (John Wiley & Sons, Inc., 2023)
"The "Panic of 1907," as it was called, is considered the third worst stock market crash in history. Historians say it lasted from January 19, 1906, through November 15, 1907. The market crash was primarily caused by a credit crunch in New York that slowly spread across the country. To try to offset the decline, the U.S. Treasury department bought $35 million worth of government bonds. The Panic of 1907 aims to discuss the drivers of this crash and the major players involved, including F. Augustus Heinze and his bank, Knickerbocker Trust, as well as what lessons we have learned and can continue to learn from the panic"--